Respuestas

2012-07-18T20:25:55+02:00

 

a) x^3-6x^2+9x= x(x²-6x+9)                      

 

b) x^3-x= x(x²+1)                                        

 

c) 4x^4-81x^2= x²(4x²-81)

d) x^3+2x^2+x=  x(x²+2x+1)

 

e) x^4+9x^3-10x^2= x²(x²+9x-10)

 

f) 3x^3-9x^2-30x=  x(3x²-9x-30) ó 3x(x²-3x-10)

 

*Espero haberte ayudado, saludos.

2012-07-19T01:32:47+02:00

a) x(x al 2 - 6x+9)

b) x(x al 2 - 1)

c)x l cuadrado (ax al cuadrado - 81)

d) x(x al 2 + 2x+1)

e) x al 2 (xal 2+9x-10

f) 3x(x al 2 - 3x-10)